Quality of life in children with thalassemia major following up at a tertiary care center in India (GOTQoL) - Ankush, Ankush; Dias, Amit; Silveira, M. P.; Talwadker, Yash; Souza, Joachim Piedade (International Journal of Contemporary Pediatrics, 2018)
Background: This study aims to measure the quality of life (QoL) scores in children with thalassemia major following up at a tertiary care center for routine blood transfusion in comparison to healthy children. Methods: A case control study design was adopted, wherein on the QoL of 36 children with thalassemia in the age group 5 to 18 following up for blood transfusion at Goa Medical College, was measured using PedsQL™ 4.0. This was compared to the QoL in age and gender matched healthy children from a government school. A higher score on a subscale indicates better quality of life on this instrument. Results: The children with thalassemia had lower mean scores on physical (67.85 vs 84.24; P <0.001), social (78.34 vs 87.95; P=0.002) and school (62.64 vs 79.48; P <0.001) functioning subscales compared to the healthy children. They also had lower mean psychosocial summary score (73.32 vs 82.01; P=0.003) and total health summary score (71.95 vs 82.57; P <0.001). The physical functioning subscale had significantly higher score among the children who were on chelation and also among the ones whose parents reported as being informed about the condition. Conclusions: The children with thalassemia have poor QoL in physical, social and school functioning domains. Improvement in QoL requires consolidated efforts on part of doctors, parents, school authorities and policy makers. These patients should be provided with low cost-effective chelation therapy. The parents need to be counselled about this disease by the treating team.